Art + Squat = X - Moore, Alan W. (Revista Estado da Arte, 2022)
This paper was written for a talk of 2012 at the Universidad Complutense in Madrid. It is greatly indebted to the researches of the SqEK (Squatting Europe [or Everywhere] Kollectiv).The experiences and researches in New York City and Europe which form the basis of my analysis here are expanded in the 2015 book Occupation Culture, and glossed by firsthand texts by squatters in the anthology Making Room. I have revised this text some for this 2021 publication, but it is firmly rooted in its moment of optimism – the movement of the squares and Occupy Wall Street. Things have changed a lot since then in this most changeable of worlds.Qual é o papel dos artistas e da arte nas ocupações? Este texto está aparado nas ideias de contracultura e "êxodo" em direção à autonomia, sendo influenciado pelo anarquismo e pela política de esquerda. Artistas não se sentem em casa no sistema capitalista. A subcultura reforça ações de resistência. Há múltiplas histórias de ocupações de natureza comunitária em países europeus. A arte nas ocupações é parte da cultura de movimento social. O texto detalha vários estudos de caso de artistas da cidade de Nova York no movimento de ocupações por lá e comenta sobre artistas no movimento de ocupações na Europa. Músicos, artistas de rua, cineastas, ativistas da mídia também estão envolvidos de forma central em ocupações. O conceito de "instituições monstruosas", a arte da prática social e a institucionalização de antigas ocupações são discutidos.